(3+3) Annulation of acetoxy allenoates with enolisable carbonyl substrates leading to fused pyrans - Chauhan, Sachin; Debnath, Shubham; Swamy, K. C. Kumara (Organic & biomolecular chemistry, 2023)
Lewis base dependent (3 + 3) annulation of delta-acetoxy allenoates with benzofuranone, pyrazolone, and Boc-protected oxindole is reported. In the presence of catalytic DBU, oxindole, benzofuranone, and pyrazolone undergo (3 + 3) annulation with delta-acetoxy allenoates via 6-exo-dig cyclisation at room temperature (25 degrees C) to afford fused pyran scaffolds. On the other hand, by employing catalytic DMAP, the reaction between N-Boc-oxindole and delta-acetoxy allenoates goes through 6-endo-dig cyclisation, leading to distinct dihydropyrans that contain an exocyclic double bond; similar products were also obtained by using benzofuranone and pyrazolone.